The Promise and Peril of Emerging Technology for Brain Enhancement - LaGrandeur, Kevin (Journal of Posthumanism, 2024)
Today’s emerging technologies provide possibilities for radical therapy for human diseases and disabilities, as well as radical enhancement and alteration of human abilities. This article discusses both the positive and negative possibilities of three current emerging technologies for therapy and bioenhancement—brain-computer interfaces, prosthetic memory, and transcranial direct current stimulation—as well as fictional narratives that prefigure these innovations. The author argues that the particular dangers of current radical emerging technologies that could enhance brain processing speed, alter or enhance memory, and affect mental states are prefigured by fictional stories that anticipate these real innovations.